Gender and the Indonesian pronouns - Steinhauer, Hein (Wacana, Journal of the Humanities of Indonesia, 2010)
The absence of a gender opposition in the Indonesian pronominal system requires special strategies in the translation from languages which do have such an opposition illustrated in the first part opf this article. In the second part the lexical and morphological means are discussed with which Indonesian expresses gender, culminating in a description of the use of perempuan and wanita, pria and laki-laki.